Menilik Perbandingan Kontribusi Pajak Pariwisata terhadap Pendapatan Asli Daerah Kota Singkawang Sebelum dan Saat Masa Pandemi Covid-19 - Rukmi, Murti Puspita; Nugroho, Yohanes Adi; Sari, Wida Arindya; Pratiwi, Wilka (Eksos, 2023)
Tourism tax is part of regional taxes which consist of restaurant tax, entertainment tax and hotel tax. Good tourism tax management can have a good impact on local governments in increasing regional independence which is reflected in local original income. March 2020, the Covid-19 pandemic was officially declared to have entered Indonesia. This has a significant impact on the economy in Indonesia. One of those affected is the tourism sector where there is a policy of temporarily closing tourist attractions. This research aims to compare the contribution of tourism tax to local revenue before and during the Covid pandemic, especially in Singkawang City, which is the best tourism city in West Kalimantan Province. The research method applied is a descriptive approach with a combination of quantitative and qualitative methods. Meanwhile, the data analysis tool applied in this research is the Paired Simple T-Test statistical test. The research results show that there is no difference between the contribution of tourism tax to Singkawang City's original regional income before and during the Covid-19 pandemic.